Evaluation of Therapies for Peripheral and Neuraxial Opioid-induced Pruritus based on Molecular and Cellular Discoveries. (August 2021) - Nguyen, Eileen; Lim, Grace; Ross, Sarah E.
Abstract : Opioids are a mainstay of treatment for pain worldwide. Pruritus, a common side effect of opioids, is a patient dissatisfier that limits their use in many clinical settings. Both parenteral and neuraxial administration of opioids frequently evoke pruritus. The ability of opioids to suppress pain while causing itch continues to perplex clinicians and researchers alike. Several mechanisms have been proposed to explain how opioids can give rise to pruritus, but specific knowledge gaps perpetuate debate. This review summarizes the clinical burden of opioid-induced pruritus and emphasizes recent discoveries of peripheral and central mechanisms for opioid-induced pruritus, particularly with respect to scientific and conceptual advances in spinal cord circuitry and mast cell biology. The mechanisms and effectiveness of existing medications used for clinical management of pruritus will be evaluated, and we will highlight the emerging preclinical utility of selective κ-opioid receptor agonists, such as nalfurafine, for the management of opioid-induced pruritus. Abstract : This review summarizes the mechanisms of peripheral and central opioid-induced pruritus and evaluates the effectiveness of existing and emerging therapies for opioid-induced pruritus based on new mechanistic insights.